An Analysis of Mathematical Literacy Ability Viewed from the Goal Orientation (Universitas Negeri Semarang, 2019)
The purpose of this study was to analyze the ability of mathematical literacy viewed from the student goal orientation in the Osborn Model with the REACT Strategy. The research method used is Mixed Methods with a concurrent embedded model of quantitative method become primary. The population in this study were all students of SMP N 14 Semarang. Meanwhile, the samples taken for this study were grade VII-I students using the Osborn Model learning with REACT Strategy (experimental class), and grade VII-E students using the Discovery Learning (control class) by purposive sampling, while the subjects of the qualitative study were 6 selected students from class VII-I consisting of two students each in high, medium, and low mastery goal and performance goal. Data collection technique was done through quantitative data collection using tests, and qualitative data collection using questionnaires and interviews. The results showed: that the average test (tvalue = 4.03 > tvalue = 1.669), the different proportional test (zvalue = 2.04 > ztable = 1.64), the average difference test (tvalue = 3.45 > tvalue) = 1.669), and the different proportional tests (zvalue = 4.21 > ztable = 1.78) Based on the results of the study, therefore it can be concluded that literacy ability of students using the Osborn Model learning with REACT Strategy were better than the students who use Discovery Learning and students with mastery goals were able to master mathematical literacy ability very well compared to students with performance goals.